(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Gout is the most common form of inflammatory arthritis worldwide and its prevalence is rising. In Switzerland, there are no data available on the characteristics and treatment of gout patients. In this study, we aimed to describe numbers of patients affected by gout and hyperuricaemia and unveil approaches Swiss primary care physicians (PCPs) use for the management. METHODS This was a retrospective observational study using electronic medical routine data provided from 242 Swiss PCPs. Included were all their patients receiving urate-lowering therapy (ULT), with a diagnostic code for gout or who had a serum uric acid (SUA) measurement. According to their disease status, patients were classified into four subgroups (normal urate, hyperuricaemia, untreated gout, treated gout). For treatment analysis, patients with SUA measurements before and after ULT initiation were included. Comorbidities and risk factors for secondary causes relevant in the context of gout were collected. Outcomes were prevalence of gout and hyperuricaemia, characteristics of patients according to subgroup, number of SUA measurements, levels of SUA and patients who reached the treatment goal of a SUA level <360 µmol/l. RESULTS We assessed 15,808 patients and classified them into the subgroups. This yielded a prevalence of 1.0% for gout and 1.2% for hyperuricaemia. 2642 patients were diagnosed with gout of whom 2420 (91.6%) received a ULT. Overall; 41.3% of patients with a gout treatment had at least one SUA measurement; 15.0% of patients with treated gout had a record of SUA measurements before and after ULT initiation; and 57.5% reached the treatment goal of <360 µmol/l after allopurinol treatment. CONCLUSION Swiss gout patients received comprehensive treatment, which is reflected in a high number of patients treated with ULT, laboratory tests per person and a high treatment success rate, although there is no systematic approach to the treatment of gout.